The application of human factors and ergonomics (HFE) to community-sport organisations in resource scarce contexts: a case study of grassroots football in Makana, Eastern Cape - Bennett, Ryan (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2021)
Background: Modern Human Factors and Ergonomics (HFE) focuses on the optimisation of complex socio-technical systems and has been challenged to contribute to broader societal issues. An example is within grassroots football organisations in resource-scarce areas such as Makana, South Africa. Through embedded participatory approaches, the research problem was co-constructed: To investigate the socio-technical system of the Makana Local Football Association (LFA). Method: A useful complex system modelling tool is that of Cognitive Work Analysis (CWA), with its 5 phases used to identify constraints and affordances. Three perspectives were adopted for the application of an adapted (to suit participant characteristics) CWA to the Makana LFA: 1) how work is prescribed by the governing body SAFA, 2) how subject matter experts (SME) disclose its current functioning, and 3) how SMEs imagine it could function. Five SMEs attended 12 three-hour workshops to complete the latter two perspectives. Results: The composite work domain analysis between work as prescribed and work as disclosed identified significant mismatches between how policymakers envision the system and how SMEs report its functioning. Key differences in perspectives included the fundamental purpose of the Makana LFA, while only four of 22 functions operate within the Makana LFA. Participants also identified key affordances for the LFA such as reorientation as a community sports organisation. Discussion: Comparison between perspectives indicated four mismatches. 1) SAFA views the LFA as the foundation of the talent identification and development infrastructure of South African football. SMEs view it as a community centred organisation. 2) A lack of human capacity is evident at the community level of Makana football. 3) Funding and assets are absent at this grassroots level. 4) The LFA relies on other stakeholders, but these relationships are not formalised. Policymakers, therefore, have a lack of knowledge of the contextual challenges faced by LFA administrators. It is recommended that SAFA view the LFA as a community sport organisation, focusing on improving human capacity, increasing funding, and formalising stakeholder networks. Furthermore, conceptual models from CWA provide explicit socio-technical system redesign recommendations. Conclusion: Large mismatches between the organising body SAFA and the actual functioning of the LFA significantly hinder the effective management and running of football at a grassroots level in resource-scarce contexts in South Africa. The perspectives approach to CWA was useful in elucidating the constraints and affordances of the Makana LFA socio-technical system and informing redesign opportunities. Systems HFE methodology is therefore well placed to contribute to broader societal issues within resources scarce contexts such as football in Makana. Furthermore, the philosophical underpinnings of systems based HFE were successful in the development of sustainable participatory research within the South African grassroots football context.
Keywords: Makana Local Football Association (South Africa); Human engineering; Soccer teams -- South Africa -- Makhanda -- Management; Soccer -- Management -- South Africa